Can monocytosis act as an independent variable for predicting deep vein thrombosis?. (15th September 2016) - Maldonado-Peña, Jeffrey; Rivera, Kelvin; Ortega, Cesar; Betancourt, M.; Lugo, Jorge Edwin; Camargo, Edinson
Abstract: Introduction: Deep venous thrombosis (DVT) is a manifestation of venous thromboembolism (VTE). It has been estimated that there are 900, 000 cases of pulmonary emboli (PE) and DVT per year resulting in 60, 000 to 300, 000 deaths. About two-thirds of VTE cases are associated with prolonged hospitalizations, emphasizing the importance of major surgery or immobilization as risk factors. Methods: Retrospective study conducted in a Metropolitan Hospital. A total of 46 records were obtained from the hospital database following the established inclusion and exclusion criteria. For the control group a total of 42 records were selected. Patients included in this study were admitted with the diagnosis of deep venous thrombosis identified either by lower leg Doppler. Results: Monocytosis with DVT, p-value was < 0.001, with an Odd Ratio (OR) 9.35 and Interval Confidence (IC) 95% (3.2–27.3). The p-value for eosinophilia with DVT was 0.092, for males with DVT the p-value was 0.35 and age related groups with DVT value was 0.720. Sensitivity of monocytosis was 67.3%, specificity 80%, positive predictive value (PPV) 79.49% and negative predictive value (NPV) 63.9%. Conclusion: This study revealed the association between monocytosis and DVT, thus patients with monocytosis are more likely to develop DVT. This evidence is consistent with previous studies establishing that monocytes could have an important role with the coagulation cascade activation and the formation of DVT. The association of monocyte count and DVT can be used in the future as a significant tool in those patients with suspected DVT to increase diagnostic yield.